(3QSGdI aj GdcjejGA (B( (3GdUfYI GdTQjaI hNhGUgG (B)s - (3NGdO Hf jRjO Hf eYGhjg Hf CHj SajGf, CHh gGTe,J (B90 (3g` s
(3ChdgG (B:s
(3bGd NGdO Hf jRjO CeG HYO aEf Gdgd JHGQc hJYGdi Ndb cd TF ebOGQ hLYd ef cd RhL HgjL eNJda GdGdhGf Ke bGd dCOe Ydjg GdSdGe (B( (3jG COe CfHFge HCSeGFge Ke Efi CYde eG dGJYdehf (B) s
(3BNQgG (B:s
(3hYed bOGei GdYLGFH ef gPG GdLfS SjQ GdGLSGe cdgG Cf jchf fMGS LOjO bO CMceJ UfYJgG hGdSdGe JeJ hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B300 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B98s
Keywords: (3GdcjejGA h GdWHjYjGJs